Prompt responses of magnetospheric whistler-mode waves to solar wind dynamic pressure pulses - Liu, Nigang; Su, Zhenpeng (Frontiers in Astronomy and Space Sciences, 2023)
Whistler-mode waves play a critical role in shaping the Earth's radiation belts, and their spatiotemporal distribution is vital for forecasting and modeling geospace weather. Previous works have extensively investigated the influences of geomagnetic activities, such as storms and substorms, on the modification of whistler-mode waves, but the direct impacts of solar wind disturbances have received relatively less attention. Recently, increasing research has highlighted the prompt impacts of solar wind dynamic pressure pulses on magnetospheric whistler-mode waves. This paper reviews the current progress in this field, specifically the prompt responses of chorus waves and plasmaspheric hiss to the solar wind dynamic pressure pulses. It will summarize the underlying mechanisms and pose some outstanding questions.